2019
DOI: 10.1093/ecco-jcc/jjz092
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes of Paediatric Patients Admitted With Acute Severe Colitis— A Multicentre Study From the Paediatric IBD Porto Group of ESPGHAN

Abstract: Background and Aim Acute severe colitis [ASC] is associated with significant morbidity in paediatric patients with ulcerative colitis [UC]. Most outcome studies in ASC since tumour necrosis factor alpha [TNFα] antagonists became available have focused on the first year after admission. The aim of this study was to characterise the longer-term outcomes of paediatric patients admitted with ASC. Methods This retrospective study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…The colectomy among patients with no flares differed substantially from that among patients with several flares during follow-up (3-40%) [2]. A recent multi-centre study of pediatric patients admitted with ASUC reported a colectomy rate of 36.4% at 5-year follow-up [15]. The colectomy rate of 26% in our series was lower than that reported in those studies.…”
Section: Discussioncontrasting
confidence: 77%
“…The colectomy among patients with no flares differed substantially from that among patients with several flares during follow-up (3-40%) [2]. A recent multi-centre study of pediatric patients admitted with ASUC reported a colectomy rate of 36.4% at 5-year follow-up [15]. The colectomy rate of 26% in our series was lower than that reported in those studies.…”
Section: Discussioncontrasting
confidence: 77%
“…26 Colectomy-free rates were 71.3%, 66.4%, and 63.6% after one, three, and five years, respectively, demonstrating that despite the introduction of anti-TNFs, the clinical outcomes of children with ASC are still poor. 26 In our cohort, children with severe UC at IFX initiation developed poorer long-term outcomes, including a higher rate of IFX failure and a higher colectomy rate, than those with moderate UC. Specifically, the Kaplan-Meier curve detected a two-year cumulative colectomy rate of 15.38% in children with severe UC versus 3.92% in patients with moderate UC.…”
Section: Discussionmentioning
confidence: 99%
“…IFX optimization strategies are particularly needed in the setting of ASC. Recently, Krauthammer et al reported the follow‐up of a multicenter cohort of children admitted for an ASC flare in the biologics era 26 . Colectomy‐free rates were 71.3%, 66.4%, and 63.6% after one, three, and five years, respectively, demonstrating that despite the introduction of anti‐TNFs, the clinical outcomes of children with ASC are still poor 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historical data report that between 4% and 17% [1][2][3] of children with UC have a colectomy by 1 year after diagnosis, rising to 20% to 26% by 5 years. 4,5 Universal or extensive colitis at diagnosis and an initial Pediatric Ulcerative Colitis Activity Index (PUCAI) score ≥ 65 1,3,6,7 have been associated with a higher risk of colectomy, as have hypoalbuminemia, 3 elevated C-reactive protein, 8 elevated erythrocyte sedimentation rate (ESR), 9 and anemia. 2,10 Early requirements for antitumor necrosis factor (TNF) α therapy 1,8,10 and a lack of complete response by 6 weeks after anti-TNFα therapy have been associated with a higher risk of colectomy.…”
Section: Introductionmentioning
confidence: 99%